Association of Lipid Profile with Preeclampsia (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Preeclampsia is a pregnancy specific disorder characterized by hypertension and proteinuria after 20 weeks of gestation. Abnormal lipid profile is known to be associated with development of symptoms of preeclampsia. Obective of the study includes evaluating the association oflipid profile with preeclampsia.Materials and methods: This case control study was carried out in the Department of Obstetrics & Gynecology, Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka, between 1st October 2017 and 30th September 2018. 46 pregnant women clinically diagnosed as preeclampsia were selected as cases (Group I) and equal number of age, parity and gestational age group matched apparently healthy normotensive pregnant women were selected as control (Group II) for the study. Fasting blood sample were collected and estimated for serum lipid profile. Demographic data and lipid profile were analyzed by using student t-test and chi square test, a p-value of